Dementia with Lewy Bodies (DLB), Parkinson's Disease (PD), and Multiple System Atrophy (MSA) Are Synucleopathies Characterized by Increased Serum Levels of Plasminogen Activator Inhibitor‑1 (PAI-1) - Angelucci, Francesco; Nedelska, Zuzana; Napravnikova Manová, Blanka; Katonová, Alžbeta; Jurášová, Vanesa; Svetlikova, Daniela; Vyhnálek, Martin; Hort, Jakub (ACS omega, 2025)
Dementia with Lewy bodies (DLB), Parkinson's disease (PD), and multiple system atrophy (MSA) are neurodegenerative disorders characterized by abnormal accumulation of α-synuclein. Plasmin is a serine protease with a role in various physiological processes, including tissue and synaptic remodeling, inflammation regulation, and modulation of neurotrophic factors. It has also been shown that plasmin is able to cleave extracellular α-synuclein in neuronal cell cultures. The plasminogen activator inhibitor-1 (PAI-1) and the tissue plasminogen activator (tPA) regulate the synthesis and activity of plasmin in the brain. We measured the serum levels of tPA and PAI-1 in 30 DLB, 10 PD, and 12 MSA patients and compared them to 10 adults (controls). tPA and PAI-1 serum protein concentrations were quantified by ELISA and compared across the groups. The findings demonstrated that PAI-1 serum levels were increased in DLB (p < 0.05), PD (p < 0.01), and MSA (p < 0.001) patients as compared to controls. In addition, MSA patients had higher PAI-1 serum levels (p < 0.01) as compared to DLB patients, showing the highest PAI-1 levels among all groups. No differences in tPA serum levels were found among groups. Our findings suggest an involvement of plasmin system in these synucleinopathies although there are some limitations due to the heterogeneity of our cohort of participants. Thus, these data must be seen as preliminary observations and further studies in larger and more homogenous cohorts are needed before drawing definitive conclusions.